How a strand of DNA launched a career. - Predd, P.P.
This paper discusses the DNA career of Michael Heller. Combining his interests in biochemistry and electronics, Heller got in on the ground floor of the biotechnology revolution and helped establish the technology behind DNA microarrays. These dime-sized devices are used to quickly analyze hundreds of DNA samples at a time, to detect genetic diseases and mutations. Also, Heller pushed the technology further. Using silicon for his substrate instead of ordinary glass, he developed a version that lets researchers move DNA molecules around electronically (most biological molecules carry a slight positive or negative electric charge). Concentrating molecules in different microarray locations in this way increases the speed and improves the efficiency of the analyses, allowing different types of genetic tests to be integrated on the same chip. With his outstanding work, he is now one of the top makers of DNA microarrays in the world.
Keywords: DNA microarrays; Biological molecules; Biotechnology revolution; Electric charge; Genetic diseases